Can everybody be well fed by 2020 without damaging natural resources? - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul; International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 1997)
This lecture discusses six actions essential to meeting global food needs without damaging the natural environment: selectively strengthening the capacity of the governments of developing countries, investing in the poor, accelerating agricultural productivity, assuring the sound management of natural resources, and expanding and realigning international development assistance. Two scenarios are used to illustrate the impacts of different courses of action taken to mitigate threats to sustainable food security.